Answer:
A' = (-2, -4)
B' = (-7, -6)
C' = (0, 0)
Explanation:
Vertices of triangle ABC:
- A = (2, -3)
- B = (-3, -5)
- C = (4, 1)
Given mapping rule:
(x, y) → (x - 4, y - 1)
This notation tells you that the x-coordinate is translated 4 units to the left, and the y-coordinate is translated 1 unit down.
Substitute the coordinates of each point into the mapping rule to find the vertices of triangle A'B'C':
⇒ A' = (2 - 4, -3 - 1) = (-2, -4)
⇒ B' = (-3 - 4, -5 - 1) = (-7, -6)
⇒ C' = (4 - 4, 1 - 1) = (0, 0)